Therapeutics utilizing cell-based interventions for type 1 diabetes mellitus - Barcala Tabarrozi, A. E. (2013)
Type 1 diabetes mellitus (T1DM) results from death of insulin-secreting β cells mediated by self-immune cells, and the consequent inability of the body to maintain insulin levels for appropriate glucose homeostasis. Probably initiated by environmental factors, this disease takes place in genetically predisposed individuals. Given the autoimmune nature of T1DM, therapeutics targeting immune cells involved in disease progress have been explored over the last decade. Several high-cost trials have been attempted to prevent and/or reverse T1DM. Although a definitive solution to cure T1DM is not yet available, a large amount of information about its nature and development has contributed greatly to both the improvement of patient's health care and design of new treatments. In this study, we discuss the role of different types of immune cells involved in T1DM pathogenesis and their therapeutic potential as targets and/or modified tools to treat patients. Recently, encouraging results and new approaches to sustain remnant β cell mass and to increase β cell proliferation by different cell-based means have emerged. Results coming from ongoing clinical trials employing cell therapy designed to arrest T1DM will probably proliferate in the next few years. Strategies under consideration include infusion of several types of stem cells, dendritic cells and regulatory T cells, either manipulated genetically ex vivo or non-manipulated. Their use in combination approaches is another therapeutic alternative. Cell-based interventions, without undesirable side effects, directed to block the uncontrollable autoimmune response may become a clinical reality in the next few years for the treatment of patients with T1DM.